Manajemen Pendidikan dalam Kacamata (Pandangan) Al-Qur’an - Dian Herdiana; Dida Hidayat; Anggun Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Al-Qur'an is a way of life for all time, which is relevant in various aspects of life. At first glance, the Qur'an discusses issues of belief, worship, morals, lawful and unlawful, but more than that, the Qur'an also discusses issues of science. Among other things related to education issues, including the scope and Management of Education. The word